Implementation of regional rice value chain upgrading strategy in West Africa - CGIAR Research Program on Rice (2020)
The regional rice value chain upgrading strategy was published and communicated to policy makers in sub-Saharan Africa and contributed to the revision and implementation of national rice development strategies (NRDS) of 32 member states of the Coalition for African Rice Development (CARD).